Regulation of Brain-Derived Neurotrophic Factor and Growth Factor Signaling Pathways by Tyrosine Phosphatase Shp2 in the Retina: A Brief Review - Abbasi, Mojdeh; Gupta, Vivek; Chitranshi, Nitin; You, Yuyi; Dheer, Yogita; Mirzaei, Mehdi; Graham, Stuart L. (Frontiers in Cellular Neuroscience, 2018)
SH2 domain-containing tyrosine phosphatase-2 (PTPN11 or Shp2) is a ubiquitously expressed protein that plays a key regulatory role in cell proliferation, differentiation and growth factor signalling. This enzyme is well expressed in various retinal neurons and has emerged as an important player in regulating survival signalling networks in the neuronal tissues. The non-receptor phosphatase can translocate to lipid rafts in the membrane and has been implicated to regulate several signalling modules including PI3K/Akt, JAK-STAT and MAPK pathways in a wide range of biochemical processes in healthy and diseased states. This review focuses on the roles of Shp2 phosphatase in regulating BDNF neurotrophin signalling pathways and discusses its cross-talk with various growth factor and downstream signalling pathways in the retina.